Evaluation of chromosomal abnormalities and common trombophilic mutations in cases with recurrent miscarriage - Karatas, Ahmet (Afr Health Sci, 2014)
BACKGROUND: Recurrent miscarriage (RM) is a frequent obstetric problem. Its' pathophysiology is poorly understood. Infections, genetic, endocrine, anatomic and immunologic problems have been suggested as causes for RM. OBJECTIVE: To evaluate the frequency of chromosomal abnormalities and 3 common thrombophilic mutations in couples with RM. METHODS: A retrospective data collection was performed for the results of the cytogenetic analysis of the couples and Methylenetetrahydrofolate Reductase (MTHFR) C677T, Factor V Leiden (FVL) G1691A and Prothrombin (PTm) G20210A mutations of the mother in 142 couples suffering from RM. RESULTS: Prevalence of FVL, MTHFR, and PTm gene mutations were similar between cases shaving 2 or ≥3 abortions (P=0.528; P=0.233; P=0.375). In patients with FVL, MTHFR and PTm gene mutations, the OR's of having ≥3 abortions when compared to having 2 abortions were 1.515 (95% CI: 0.414–5.552), 0.573 (95% CI: 0.228–1.441), and 2.848 (95% CI: 0.355–22.871). All cases with PTm mutation had ≥3 abortions and all abortions occurred between 6–8 gestational weeks. CONCLUSION: Chromosomal abnormalities and thrombophilic mutations (especially PTm) seem to have an important role in RM. Additional larger studies involving investigation of more genes that may have a role in pregnancy are needed to assess this association.